2022
DOI: 10.1007/s10753-022-01631-2
|View full text |Cite
|
Sign up to set email alerts
|

MiR-26a Reduces Inflammatory Responses via Inhibition of PGE2 Production by Targeting COX-2

Abstract: MicroRNAs are small non-coding RNA regulatory molecules that play an important role in the development and function of immune cells. MicroRNA-26a (miR-26a) exhibits anti-inflammatory immune effects on immune cells. However, the exact mechanism by which miR-26a plays an anti-inflammatory role remains unclear. Here, we report that miR-26a reduces inflammatory response via inhibition of prostaglandin E2 (PGE2) production by targeting cyclooxygenase-2 (COX-2). We found that miR-26a was downregulated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Interestingly, from this list miR‐15a‐5p and miR‐31‐5p appeared in two or more studies 56,57,73,78,82,84,86 and could potentially serve as biomarkers for disease severity. Table 3 summarises the targets and principle cellular pathways associated with miRNAs regulated during Inf vs C and S vs C stages and cited previously 46,56,73,88–120 . Most of the miRNAs were involved in targeting virus‐host interactions, viral replication, and host‐immune responses.…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, from this list miR‐15a‐5p and miR‐31‐5p appeared in two or more studies 56,57,73,78,82,84,86 and could potentially serve as biomarkers for disease severity. Table 3 summarises the targets and principle cellular pathways associated with miRNAs regulated during Inf vs C and S vs C stages and cited previously 46,56,73,88–120 . Most of the miRNAs were involved in targeting virus‐host interactions, viral replication, and host‐immune responses.…”
Section: Resultsmentioning
confidence: 97%
“…In OA patients, we also noticed correlations between miR-26 and miR-126. Despite the antifibrotic properties of miR-26, different studies demonstrated its significance in skeletal muscle differentiation and regeneration [ 42 ] or reduction of inflammatory responses [ 43 ]. Therefore, it is possible to hypothesize that these roles are associated with a positive correlation between miR-26 and serum IL-21 concentration in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Strillacci et al, 2010). Several miRNAs associated with COX-2 are implicated as potential targets or therapies in inflammatory processes and breast cancer brain metastases (Harati et al, 2020;T. Yu et al, 2022).…”
Section: Ancient Remedies To Modern Therapeutics: Pharmacological Inh...mentioning
confidence: 99%
“…miRNAs, small interfering RNA (siRNA), and short hairpin RNAs (shRNA) can be used for targeted knockdown of COX‐2, a much more selective method of targeting compared to coxibs (A. Strillacci et al, 2010). Several miRNAs associated with COX‐2 are implicated as potential targets or therapies in inflammatory processes and breast cancer brain metastases (Harati et al, 2020; T. Yu et al, 2022). miRNAs have regulatory functions in multiple branches of the AA signaling pathway, including the cyclooxygenase pathway as well as the lipoxygenase pathway.…”
Section: Introductionmentioning
confidence: 99%